The Efficiency of Decentralised and Devolved Government: A Framework - Alex Christie; Kim Swales (European Regional Science Association (ERSA), 2006)
A wide range of geographically decentralised governance structures exists across countries (Ter-Minassian, 1997). These differences in administrative and constitutional mechanisms come about, at least partly, by historical accident and wider political factors. However, in this paper we focus on the more narrowly defined efficiency implications of such arrangements. This is useful for identifying the motives that might underlie particular administrative set ups and the possible efficiency losses associated with specific forms of decentralisation or devolution. In particular, we develop a framework that allows a comparison of the effectiveness of implementing policy through three alternative systems. These are: a centralised; a decentralised; and a fully devolved structure. In this analysis we build on the work of Canes-Wrone et al, (2001) and Maskin and Tirole (2004) on representative democracy. The novelty is that we place this analysis in the context of a potentially decentralised or devolved regional administration. We find that the choice of appropriate administrative form depends upon the degree of homogeneity between regions, the relative efficiency of regional decision makers and their time discount rate.
Keywords: 330